Issues and Conflicts in Balochistan: Implications for Pakistan - Dr. Muhammad Muzaffar; Dr. Imran Khan; Dr. Zahid Yaseen (Journal of Political Studies, 2021)
Strategically situated Balochistan, its immense assets and exceptionally inconceivable area have expanded its importance in the world. The external forces are appreciating its most easily open corridor to the huge resources of Central Asian States. From the 1947, the misunderstanding rose among the Pakistani government and Baloch individuals. Pakistan interplanetary toward Balochistan has exacerbated the condition in region especially with respect to the financial and social advantages of Baloch individuals which brought about blood insurgence in the part. In the use of its huge resources for the revenue of Pakistan and especially the Balochi peoples, insurgency has been the crucial difficulty. The brokenness of the election based procedure and interventions by the army especially in military governments has motivated the grievances of Baloch societies. In this article, we present the history of Baloch conflicts and other major issues of Balochistan and also draw some implications for the Pakistan.